EXPERIMENTAL MANUFACTURE OF THE FOAM GLASS GRAVEL FROM GLASS WASTE AND SILICON CARBIDE ON A 10 kW-MICROWAVE OVEN - LUCIAN PAUNESCU; SORIN MIRCEA AXINTE; FELICIA COSMULESCU (Journal of Engineering Studies and Research)
The work presents the results of the experimental manufacturing process on a 10 kW-microwave oven of foam glass gravel (FGG) from glass waste (98 wt. %) and silicon carbide (2 wt. %), the sintering/foaming temperature being varied between 910-930 ºC. The paper originality is the significant increase (about 8 times) of the amount of glass-based raw material foamed by the unconventional heating compared to the previous experiments. The main features of the FGG experimental samples were: bulk density between 0.26-0.31 g·cm-3, compressive strength between 8.5-9.7 MPa and thermal conductivity between 0.068-0.077 W/mK, suitable for their use as thermal insulation material in several applications in construction.